Regional Tourism In Banten Potential And Development - Mafrudoh, Lut (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The province of Banten, located at the western tip of Java Island, has tremendous tourism potential with various natural, cultural, and historical destinations. This article examines Banten's tourism potential, including beach tourism, cultural tourism, religious tourism, and nature conservation. The research aims to explore the untapped tourism potential and highlight the need for infrastructure development and tourism promotion to enhance Banten's appeal on a regional and national scale. The method used in this study is a literature review and secondary data analysis from local government reports and the Ministry of Tourism. The discussion results emphasize the importance of integrated management and promotion strategies to increase tourist visits and boost the local economy. This article provides strategic recommendations for the sustainable development of tourism in Banten.